An overview of safety for laboratory testing of lithium-ion batteries. (May 2021) - Fantham, Thomas L.; Gladwin, Daniel T.
Abstract: Secondary Lithium-ion batteries are widely used in a variety of sizes from single cells in personal electronics, to large packs in Electric Vehicles (EVs), and very large packs in grid-scale storage. With the number of applications increasing, this brings more laboratory testing of such batteries. A number of papers discuss the safety intrinsic to cells, however, excluding EVs there is little discussion of cycling larger, multi-cell packs. This paper considers safe laboratory testing of commercial high capacity single cells and multi-cell battery packs. Using the hazards and failure modes that can occur, appropriate control measures are proposed, including fuses, contactors and good practice in system design. Suitable enclosures and fire suppression are also recommended should these measures fail. For single cells without a BMS, a separate protection circuit is presented utilizing analogue components for reliability.